2015
DOI: 10.1111/rec.12319
|View full text |Cite
|
Sign up to set email alerts
|

Near‐natural methods promote restoration of species‐rich grassland vegetation—revisiting a road verge trial after 9 years

Abstract: The present loss of species-rich grasslands makes it vital to restore these valuable habitat types, including novel habitat variants such as road verges. Due to the lack of knowledge on long-term outcomes of restoration initiatives, well-designed studies comparing different restoration methods are needed. In this study, we examined fine-scale vegetation recovery patterns over 9 years in a field experiment with several near-natural restoration methods (adding local seed mixtures, transferring hay from local gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 50 publications
(85 reference statements)
2
26
0
Order By: Relevance
“…We only found a small advantage of deep tillage compared with shallow tillage not justifying the higher negative impact on soil structure and biota. Our study also confirmed that longterm monitoring is required to evaluate restoration success in productive grasslands (Auestad et al, 2016;Baasch et al, 2016). Within usual study periods of three to four years, results may be misleading since self-thinning due to seedling mortality reduced target plant number in the first years but later on secondary spread increased abundance.…”
Section: Discussionsupporting
confidence: 74%
“…We only found a small advantage of deep tillage compared with shallow tillage not justifying the higher negative impact on soil structure and biota. Our study also confirmed that longterm monitoring is required to evaluate restoration success in productive grasslands (Auestad et al, 2016;Baasch et al, 2016). Within usual study periods of three to four years, results may be misleading since self-thinning due to seedling mortality reduced target plant number in the first years but later on secondary spread increased abundance.…”
Section: Discussionsupporting
confidence: 74%
“…The minimum data requirement for M A models is a time series of at least three temporal recordings. An additional danger of obtaining mis‐specified models from sparse data appears when compositional dissimilarity from the restoration target increase shortly after disturbance (Auestad, Rydgren, & Austad, ; Kirmer, Rydgren, & Tischew, ). In succession, random variation in species composition between years may override a weak temporal trend.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the pervasiveness of roads throughout rural landscapes, road verges have the potential to have a significant impact on landscape‐level biodiversity, both positively and negatively, with national governmental agencies providing guidelines for appropriate road‐verge management (Bromley, McCarthy, & Shellswell, 2019; Venner, 2006; Swedish Transport Administration, 2019). To promote biodiversity of grassland plant species, mowing more than once per year and removing the resulting material has been found to be most effective (Jakobsson, Bernes, Bullock, Verheyen, & Lindborg, 2018), while active restoration such as seed sowing can also be used to increase the number of target species present (Auestad, Rydgren, & Austad, 2016). However, due to the increased costs of these more intensive methods of management, it is not financially or practically feasible to implement them on all road verges in all landscapes.…”
Section: Introductionmentioning
confidence: 99%